PERWATAKAN DALAM NOVEL KOMSAS “DI SEBALIK DINARA”: ANALISIS TEORI RELEVAN = Characteristik in Novel “Di Sebalik Dinara”: A RelevanTheory Analysis - Srikandi Saemah, Samaon; Mary Fatimah, Subet (Universiti Sultan Zainal Abidin, 2020)
Elements of Malay Literature in the Malay Language (ML) was introduced in the learning of Malay Language in secondary schools. There are five main genres in the (ML) study which are traditional poetry, modern poetry, traditional prose, modern prose and novel. Novel is one of the (ML)genres featuring a variety of characters, questionnaire, community culture, values and teaching. Throughout reading the novel, the reader can understand various situations that can give the reader a variety of insights that can enhance the reader's awareness. This study will analyze the characteristics in Di Sebalik Dinara‘s by Dayang Nor. This study is a qualitative study which is a text analysis. In analyzing this novel the researcher will apply the Relevance Theory (TR) approach to cognitive effects and information processing efforts to help the reader understand the character’s characteristics in the novel. The character traits in the novel are analyzed in TR and Bridging Cross Reference (BCR)an elaborate and implicit manner to help the reader understand the characteristic of the character in Di Sebalik Dinara. The results of the TR and RRS analysis can be concluded that the characters in this novel are illustrated one who are self-reliant, responsible, do not act hastily and always cautious in decision-making.